TRUST AS A MODERATOR AND GREEN PERCEIVED VALUE AS A MEDIATOR IN THE RELATIONSHIP BETWEEN PRODUCT PERCEPTION AND GREEN PURCHASE INTENTION - Viniyati Maftuchach; Nandan Limakrisna; Agus Setyo Pranowo (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
The increasing environmental awareness among consumers has prompted companies especially in the bottled water industry to adopt green marketing strategies, including the use of eco-labels and sustainable packaging. Despite these efforts, the effectiveness of such strategies in influencing green purchase intention remains inconsistent across different consumer segments. This study aims to investigate the effects of green product awareness and eco-labels on green purchase intention, with green perceived value serving as a mediating variable and trust as a moderating variable. Employing a quantitative research approach, data were collected from 314 Environmental Engineering students in DKI Jakarta through proportional random sampling. Structural Equation Modeling (SEM) was used to analyze the relationships between variables. The model demonstrated good overall fit based on various goodness-of-fit indices. The findings reveal that both green product awareness and eco-labels significantly influence green purchase intention and green perceived value. Green perceived value also directly enhances green purchase intention and mediates the relationship between eco-labels and purchase intention. However, the mediation effect of green perceived value between green product awareness and green purchase intention was found to be insignificant. Furthermore, trust was shown to strengthen the influence of both green product awareness and eco-labels on green perceived value. This study concludes that enhancing consumers' trust and perceived value of environmentally friendly products is critical for driving green purchase intention, especially among young and environmentally conscious individuals. The findings contribute to the literature by clarifying the role of perceived value and trust in green consumer behavior. Practically, the study suggests that companies should not only increase awareness and labeling but also foster trust and clearly communicate the environmental value of their products. This integrated strategy is vital for shaping sustainable consumption patterns in emerging markets.